Application of the TOPSIS Method (Technique for Order Preference by Similarity to Ideal Solution) in Product Selection - Rosa, Rosa; Sari Siregar (SEAN Institute, 2024)
In an era of increasingly fierce business competition, the right product selection is one of the company's successes. The TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method offers a systematic approach to evaluate various product alternatives based on predetermined criteria. This research aims to apply the TOPSIS method in product selection, focusing on factors such as price, quality, and features. The results of the analysis show that this method improves the efficiency and objectivity of decision-making, allowing companies to identify the best products that are close to the ideal solution. In addition, the use of TOPSIS also increases the transparency of the evaluation process, supports adaptation to market changes, and assists companies in achieving competitive advantage. These findings confirm the importance of the TOPSIS method as a tool for intelligent, data-driven decision-making in a dynamic business context.